Measurement Method of IGBT Thermal Resistance Based on Structure Function - FENG Qin; LI Shiping; CHEN Yan; WAN Chaoqun; LI Yi (Kongzhi Yu Xinxi Jishu)
Based on the structure function theory, it studied the thermal characteristics between the same IGBT case and the different baseplate interfaces, and found separation point of structure functions, by which thermal resistance between the internal PN junction and the case of IGBT module was got. Besides, through comparing the structures of IGBT module with different contact materials, the proper contact material was selected. The study results show that the structure function is a powerful method to analyze the thermal characteristics of high power IGBT modules.